ANALISIS SISTEM AGRIBISNIS AYAM BROILER POLA KEMITRAAN DI KECAMATAN STM HILIR KABUPATEN DELI SERDANG - Kurniawan, Media Agus; Rusdhi, Alfath; Fachrozi, Iqal (Scenario (Seminar of Social Sciences Engineering and Humaniora); 2020, 2021)
The aim of this research are to know of broiler chicken agribusiness system and its income plasma breeders. That data obtained on analyzed kualitatif descriptive and kuantitatif descriptive. Research is done at husbandry of Kecamatan STM Hilir, Kabupaten Deli Serdang. Based on the research in know that the laying chicken farm in STM is an agribusiness system involving agribusiness subsystem ranging from upstream to downstream, including supporting subsystem. The level of income in agribusiness chicken broiler in STM Hilir reached R / C ratio of 1.19 and included a profit categories.